2018
DOI: 10.1016/j.bspc.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of time-domain, frequency-domain and non-linear analysis for distinguishing congestive heart failure patients from normal sinus rhythm subjects

Abstract: Comparison of time-domain, frequency-domain and non-linear analysis for distinguishing congestive heart failure patients from normal sinus rhythm subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…İşler et al reported that the combination of the classical HRV indices with indices obtained from wavelet entropy calculations could significantly improve the performance of the HRV analysis in CHF screening [ 32 ]. In this paper, the LF/HF ratio is significantly distinguished between the normal group and CHF group ( Figure 5 ), which is consistent with other findings studying HRV features of CHF [ 33 , 34 , 35 , 36 ]. However, they only focused on decomposing independent frequency components of HRV but neglected a complex interaction between the independent frequency components of HRV.…”
Section: Discussionsupporting
confidence: 92%
“…İşler et al reported that the combination of the classical HRV indices with indices obtained from wavelet entropy calculations could significantly improve the performance of the HRV analysis in CHF screening [ 32 ]. In this paper, the LF/HF ratio is significantly distinguished between the normal group and CHF group ( Figure 5 ), which is consistent with other findings studying HRV features of CHF [ 33 , 34 , 35 , 36 ]. However, they only focused on decomposing independent frequency components of HRV but neglected a complex interaction between the independent frequency components of HRV.…”
Section: Discussionsupporting
confidence: 92%
“…Sample entropy (SampEn) and fuzzy measure entropy (FuzzyMEn) are often used as measures for the analysis of the complexity of HRV signals [14][15][16][17]. Usually, SampEn and FuzzyMEn are influenced by the parameters of embedding dimension m and tolerance threshold r [16,17]. In this paper, the best combination of m and r for SampEn and FuzzyMEn were obtained by statistical significance analysis.…”
Section: Non-linear Hrv Featuresmentioning
confidence: 99%
“…The linear features are the signal parameters in time-domain, frequency-domain, and time-frequency domain [7][8][9]. In order to reveal other valuable information contained in the IBI signal, some researchers have used the complexity analysis method to extract nonlinear indicators [10][11][12][13][14][15][16][17][18][19][20]. In 2003, Asyali et al [21] applied Bayesian classifiers and nine long-term measurements for CHF discrimination with an accuracy of 93.24%.…”
Section: Introductionmentioning
confidence: 99%
“…Power spectral density (PSD) is nothing but the power of a signal is distributed over frequency (or) can be defined as distribution of power into frequency components forming that as signal. PSD is a type of random signal which is independent of time [2,12]. Power spectral density is used differentiate the frequency component variations in the three different ECG signals in which one is Normal ECG and the other two are ECG of abnormal conditions of the heart.…”
Section: Power Spectral Density (Psd)mentioning
confidence: 99%